2019
DOI: 10.1152/ajpregu.00184.2019
|View full text |Cite
|
Sign up to set email alerts
|

Impact of acute antioxidant administration on inflammation and vascular function in heart failure with preserved ejection fraction

Abstract: Background One of the many unique features of heart failure with preserved ejection fraction (HFpEF) is the presence of multiple comorbidities, many of which are characterized by a pro‐inflammatory and pro‐oxidant state which may impair vascular function. This axis of inflammation, oxidative stress, and vascular function has been well described in other patient populations, whereby increases in reactive oxygen species lead to eNOS uncoupling, reduced nitric oxide (NO) bioavailability, and ultimately, impaired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 45 publications
3
18
0
Order By: Relevance
“…A pro-inflammatory state that leads to the pathophysiology of HFpEF has been recently emphasized ( Paulus and Tschope, 2013 ; van Empel and Brunner-La Rocca, 2015 ; van Sanders-Wijk et al, 2015 ; Riba et al, 2017 ; Ratchford et al, 2019 ). We were interested in determining whether RES can decrease HFpEF-induced cardiac inflammatory response.…”
Section: Resultsmentioning
confidence: 99%
“…A pro-inflammatory state that leads to the pathophysiology of HFpEF has been recently emphasized ( Paulus and Tschope, 2013 ; van Empel and Brunner-La Rocca, 2015 ; van Sanders-Wijk et al, 2015 ; Riba et al, 2017 ; Ratchford et al, 2019 ). We were interested in determining whether RES can decrease HFpEF-induced cardiac inflammatory response.…”
Section: Resultsmentioning
confidence: 99%
“…Fortunately, there is evidence for the ‘reversibility’ of vascular dysfunction associated with elevated oxidative stress. Indeed, our group has demonstrated the efficacy of acute oral AOx administration to improve brachial artery FMD and favourably affect both oxidative stress and endogenous AOx capacity in several cohorts, including the elderly (Wray et al., 2012) and patients with chronic obstructive pulmonary disease (Ives et al., 2014; Rossman et al., 2013) or heart failure with preserved ejection fraction (Ratchford et al., 2019). Conversely, we recently demonstrated that acute AOx administration does not improve FMD in patients with HFrEF (Witman et al., 2012a), suggesting that perhaps a longer duration of AOx administration, as conducted in this investigation, might be warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, there is evidence for the 'reversibility' of vascular dysfunction associated with elevated oxidative stress. Indeed, our group has demonstrated the efficacy of acute oral AOx administration to improve brachial artery FMD and favourably affect both oxidative stress and endogenous AOx capacity in several cohorts, including the elderly (Wray et al, 2012) and patients with chronic obstructive pulmonary disease (Ives et al, 2014;Rossman et al, 2013) or heart failure with preserved ejection fraction (Ratchford et al, 2019).…”
Section: Mechanisms Of Vascular Dysfunction In Patients With Hfrefmentioning
confidence: 96%
See 1 more Smart Citation
“…The value of fractional shortening (FS) is widely used to assess left ventricular dysfunction and often decreased after myocarditis [9]. On the other hand, preserved EF [10] is associated with predominant inflammation and oxidant stress.…”
Section: Introductionmentioning
confidence: 99%